Analisis Semiotika Rolland Barthes Dalam Simbol Pada Seleksi Tilawah Al-Qur’an di Indonesia - Nia Kurniasih; Dadan Rusmana; Wildan Taufiq (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The study of this research is about the meaning and structure that exist in the Al-Qur'an Musabaqah festival in Indonesia with the analytical knife using Rolland Barthes' semiotic theory. In his semiotic analysis, Rolland Barthes describes the meaning of denotation, connotative meaning and myths regarding the meaning and structure of the Musabaqah recitations of the Qur'an which are contained in the Musabaqah Al-Qur'an festival in Indonesia, to be precise taking samples from one of the participants in the Musabaqah Recitations of the Koran at the West Java level in 2023. The research method used by the author is a qualitative-interpretive method with data collection techniques, namely documentation by searching, collecting and compiling data from various sources that are relevant to research-related problems. As for the results of Rolland Barthes's semiotic study on the meaning and structure of the recitations of the Qur'an Musabaqah recitations of the Qur'an in Indonesia, the writer found several symbols which include: praying, reciting isti'adzah, basmalah, intonation in reading the words in particular, the use of nagham and qira'at schools, to ethics in dress and ethics towards the Koran.